Does religion make you sick? Evidence of a negative relationship between religious background and health - Niclas Berggren; Martin Ljunge (Research Institute of Industrial Economics (IFN), 2017)
Religious beliefs and practices influence individual lives and societies in many ways. We study how religion affects self-assessed health, which in turn is important for both individual well-being and productivity. A religious background predicts worse health. As the previous literature has not been able to rule out reverse causality, we apply a novel method that does. The health of the children of immigrants in 30 European countries is related to different measures of religiosity in their mothers' birth countries. Since religiosity in the mothers' birth countries predicts children's religiosity (through transmission in the family), we can use the former as a measure of the latter. Moreover, the children's health arguably cannot affect the religiosity of their mothers' home countries (measured several decades earlier).Furthermore, the negative relationship between religious background and health is robust to accounting for a range of individual and ancestral country characteristics, to excluding the most and least religious ancestral countries, and to accounting for systematic differences across ancestral continents. The negative relationship, which we also find in U.S. data, suggests that the positive correlations between health and religiosity in the earlier literature are not due to religion promoting health.
Keywords: I19; Z12; 330; Health; Religion; Children of Immigrants